From Sadat to Saddam : the decline of American diplomacy in the Middle East - Dunford, David J. (Potomac Books, An imprint of the University of Nebraska Press, 2019)
From Sadat to Saddam: The Decline of American Diplomacy in the Middle East is a first-hand account of 30 years in the diplomatic trenches of US Middle East policy. The work reveals that the decline of U.S. diplomatic effectiveness well predates the arrival of the Trump administration.